2017
DOI: 10.1021/acs.orglett.7b02942
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Fluorinated Sugar Amino Acid Derived α,γ-Cyclic Peptides into Transmembrane Anion Transport

Abstract: Syntheses of fluorinated sugar amino acid derived α,γ-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C and C symmetric flat oval- and triangular-ring shaped β-strand conformations, respectively, which appear to self-assemble into nanotubes. The α,γ-cyclic hexapeptide (EC = 2.14 μM) is found to be a more efficient ion transporter than α,γ-cyclic tetrapeptide (EC = 14.75 μM). The anion selectivity and recognition of α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
(21 reference statements)
0
28
0
Order By: Relevance
“…Inspired by our recent ion transport studies with fluorinated acyclic and cyclic sugar derived peptides [1718], we investigated the ion transport activity of 1 and 2a across lipid bilayer membranes. In this study, the collapse of the pH gradient (pH out = 7.8 and pH in = 7.0), created across egg yolk ʟ-α-phosphatidylcholine (EYPC) vesicles with entrapped 8-hydroxypyrene-1,3,6-trisulfonic acid trisodium salt (HPTS) dye (i.e., EYPC-LUVsHPTS) [5761] was monitored by measuring the fluorescence intensity of the dye at λ em = 510 nm (λ ex = 450 nm) with time (Figure S11, Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by our recent ion transport studies with fluorinated acyclic and cyclic sugar derived peptides [1718], we investigated the ion transport activity of 1 and 2a across lipid bilayer membranes. In this study, the collapse of the pH gradient (pH out = 7.8 and pH in = 7.0), created across egg yolk ʟ-α-phosphatidylcholine (EYPC) vesicles with entrapped 8-hydroxypyrene-1,3,6-trisulfonic acid trisodium salt (HPTS) dye (i.e., EYPC-LUVsHPTS) [5761] was monitored by measuring the fluorescence intensity of the dye at λ em = 510 nm (λ ex = 450 nm) with time (Figure S11, Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 99%
“…Over the last several years, synthetic peptides are known to play a significant role in the design of artificial ion transport systems [1316]. Recently, our group has synthesized fluorinated acyclic and cyclic peptides from C-3 fluorinated ᴅ-glucofuranoid amino acids and demonstrated their selective anion transport activity [1718]. In continuation of our interest in sugar-derived cyclic peptides [19], we aimed to synthesize cyclic peptides I and II from the corresponding linear di- and tetrapeptides, however, we obtained an oxazolone ring containing pseudo peptides 1 and 2a, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[32,68] As an alternative to fluorinated hydrophobic tails and amino acids, other groups have chosen to incorporate fluorine into the backbone of cyclic peptides to fine tune their conformational states (Figure 2, right). [36,69] Utilizing cyclic-RGD as a template, a commonly employed bioactive ligand for α V β 3 cellular integrins, [70][71] Au and co-workers exploited stereoselective fluorination to influence the secondary structure and bioactive properties of the cyclic peptide. [69] For example, mass spectrometry and NMR studies revealed that incorporation of backbone-fluorinated γ-amino acids enhanced or reduced peptide macrocyclization efficiency, dependent on the fluorine-induced shape, and accessed novel high-energy geometries with unique cis-trans conformations.…”
Section: Methods Of Peptide Fluorination and Their Emergent Propertiesmentioning
confidence: 99%
“…When incorporated into amino acids, or appended to peptide scaffolds, fluorination leads to the emergence of an entirely new class of biopolymers that are now being employed as novel biosensors, molecular probes, and enzyme inhibitors. [36][37][38][39][40][41] More recently, and as will be focused on in this review, organofluorine self-assembling peptides can be used to readily tune the chemical, electronic, and mechanical properties of nano-, micro-, and macroscale biomaterials. Enhanced proteolytic and thermal stability are additional advantages intrinsic to fluorinated peptide-based scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Some years ago, we showed that cyclic γ‐amino acids ( cis ‐3‐aminocycloalkanecarboxylic acids, γ‐Acas) alternated with α‐amino acids (α,γ‐CPs) can also form SCPNs following the same principles described above (Scheme ) . These and other peptides containing γ‐Acas can be designed from the original d,l ‐α‐CPs by simply replacing any α‐amino acid with a γ‐residue of equivalent chirality . For instance, l ‐amino acids can be replaced with (1 R ,3 S )‐Acas while the (1 S ,3 R )‐isomers would substitute the d ‐α‐residues.…”
Section: Introductionmentioning
confidence: 99%